The Economic Geography of Trade Production and Income: A Survey of Empirics. - Overman, H; Redding, S; Venables, A (CEPR, 2001)
This Paper surveys the empirical literature on the economic geography of trade flows, factor prices, and the location of production. The discussion is structured around the empirical predictions of a canonical theoretical model. We review empirical evidence on the determinants of trade costs and the effects of these costs on trade flows. Geography is a major determinant of factor prices, and access to foreign markets alone is shown to explain some 35% of the cross-country variation in per capita income. The Paper documents empirical findings of home market (or magnification) effects, suggesting that imperfectly competitive industries are drawn more than proportionately to locations with good market access. Sub-national evidence establishes the presence of industrial clustering, and we examine the roles played by product market linkages to customer and supplier firms, knowledge spillovers, and labour market externalities.